The FSHR Polymorphisms Association With Polycystic Ovary Syndrome in Women of Erbil, Kurdistan in North of Iraq - Baban, Aesha Sh. Sh.; Korsheed, Sabah H.; Al Hayawi, Anas Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Polycystic ovary syndrome (PCOS) is an endocrine disorder in women during fertilization age that reflects changing clinical symptoms. The genetic concept of PCOS is unclear and no significant genetic association with PCOS has been established. The level of Follicle stimulating hormone FSH is encoded by FSH receptor (FSHR) and abnormal FSHR affects follicle cogenesis and ovary and consist of 9 introns, 10 exons, and the region of chromosome promoter at 2p21. Sample of 93PCOS patients and 52 controls were collected from Province of Erbil in north of Iraq. Genomic DNA was extracted from the blood and genotype dissected was improved for the two population of study using PCR-RFLP with the restriction enzyme Eam1105I. The genotype distributions and allele frequency of Ala307Thr polymorphisms of FSHR were not statistically various between the controls and the PCOS patients. Significant elevation of body mass index with all genotype of PCOS was found when compared with controls. There were statistical differences in the BMI and most of the serum hormone and lipid profile parameters including LH, total testosterone, fasting glucose, Cholesterol, HDL and LDL, there were significant various in FSH and LH levels of hormones and HDL, LDL and VLDL with PCOS group conveying different genotypes of Ala307Thr polymorphisms. The variant of Ala307Thr was not associated with PCOS in Kurdistan women; there was no relationship between the POCS and gene of FSHR polymorphism at codons 307. There was a significant difference in FSH and LH levels with PCOS patients conveying different genotypes of Ala307Thr polymorphism.